The History of EAFIT Children's University (2015)
A graphic report recalls moments from the first decade of the Program. Images showing the relationships between children and young people, and EAFIT's scientific and research knowledge. Record of emotions and experiences in the workshops of MeetingQquestions and Expeditions to Knowledge.